2001
DOI: 10.2174/1381612013398374
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of VIP: A Review and Therapeutical Perspectives

Abstract: Vasoactive intestinal peptide (VIP) is a neuropeptide with a broad distribution in the body that exerts very important pleiotropic functions in several systems. The present work reviews the immunology of VIP. Being daring, this neuropeptide could be included in the group of cytokines since it is produced and secreted by different immunocompetent cells in response to various immune signals, plays a broad spectrum of immunological functions, and exerts them, in a paracrine and/or autocrine way, through three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
138
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 151 publications
(199 reference statements)
4
138
0
1
Order By: Relevance
“…An abundant number of studies have consistently demonstrated potent immunomodulatory and antiinflammatory effects of exogenous administration of VIP (and related neuropeptides) in a variety of animal models of inflammatory disease, providing a solid basis for its potential use as a therapeutic agent (1)(2)(3)(6)(7)(8)(9)27). Several studies in the murine model of collagen-induced arthritis have shown that VIP or PACAP potently inhibits inflammatory and autoimmune components, protecting the joints from structural damage (5,6,28).…”
Section: Discussionmentioning
confidence: 99%
“…An abundant number of studies have consistently demonstrated potent immunomodulatory and antiinflammatory effects of exogenous administration of VIP (and related neuropeptides) in a variety of animal models of inflammatory disease, providing a solid basis for its potential use as a therapeutic agent (1)(2)(3)(6)(7)(8)(9)27). Several studies in the murine model of collagen-induced arthritis have shown that VIP or PACAP potently inhibits inflammatory and autoimmune components, protecting the joints from structural damage (5,6,28).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PACAP was reported to exert beneficial effects on clinical and pathological manifestations of EAE, probably through suppression of antigen presenting cell functions (Kato et al, 2004). VIP and PACAP exert a number of effects in the central nervous system (CNS) that could generally be regarded as being anti-inflammatory and neuroprotective (Gressens et al, 1997;Gozes et al, 1997;Gomariz et al, 2001). Upon axotomy, expression of PACAP is rapidly induced (Mulder et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Vasoactive intestinal polypeptide (VIP) is a neuropeptide that contributes to regulation of intestinal secretion and motility, of exocrine and endocrine secretions (Fahrenkrug 1993), and to homeostasis of the immune system (Gomariz et al 2001). The effects of VIP are mediated through interaction with two receptor subclasses named VPAC 1 and VPAC 2 receptors .…”
Section: Introductionmentioning
confidence: 99%